Qualidade do cuidado e contexto de trabalho do profissional de enfermagem em um hospital oncológico - FAQUIM, Ana Cláudia de Moraes (2014)
The demand for quality health is higher and health institutions need to improve their processes. In this context, we highlight nursing, who is faced with the need to improve their actions. The assessment of quality through indicators favors patient safety since the search for ever greater improvement in activities developed by the team. In this case assess the work context is extremely important for achieving quality in activities, and promote changes in the pursuit of a favorable working environment. The research objective is to evaluate the quality of care and the work context of nursing staff in an oncology hospital. It is a quantitative, observational study with a prospective longitudinal design to evaluate nursing care, and crosssectional design to evaluate the work context. This study was conducted in facilities of hospitalizations of Clinical Oncology and Intensive Care Unit of the Oncology Hospital, in Uberaba-MG. Forty nurses were interviewed and assessed indicators of 105 adult cancer patients. Data were collected in the period April-June 2014. In collecting an instrument based on indicators for evaluation of nursing care was used, and the Scale for Assessment of Work Context applied to professional nursing units of study. This study was approved by the Ethics Committee in Research of the Federal University of Triangulo Mineiro under Opinion No. 580.365/2014. Data from the evaluation of nursing care were presented in the form of distribution of absolute and relative frequencies. For evaluation of the work context to mean and median, standard deviation and maximum and minimum values was performed. The comparison between groups, Student's t test was performed. To investigate associations used the Pearson correlation. The average age of patients was 64.4 years, predominantly male patients. The performance for the nursing staff in the ICU was 67.4% and the unity of Clinical Oncology, 52.95% both classified as insufficient assistance. The average age of nurses was 32.5 years. Predominated technical nursing female and married sex. Of the total participants, 60.0% had more than one job. The average of the factors in the unit of Clinical Oncology was: Working Conditions (2.27), Labour (3.53) and Socio-Professional Relationship (2.02), with the Labour critical result and the other two factors satisfactory results; And in the Intensive Care Unit: Working Conditions (2.55), Labour (3.65) and Socio-Professional Relationship (2.36), classifying the work context of the three factors as critical, indicator-limit situation. Compared to the results it was possible to detect skills and limitations, identifying outbreaks in the context of work that need attention, proposing pipelines to ensure the quality of care.